What is the potential impact on boys and girls of the new 2017 GCSE English Language specification and exam arrangements? - Ingrouille, Lisa (2018)
In recent years, there have been significant changes to the General Certificate of Secondary Education (GCSE) which is generally taken by students at the end of compulsory education at the end of Key Stage 4 in England, Wales and Northern Ireland. The recent reformation of the GCSE English Language qualification has led to a change in how it is assessed with a single tier of entry; and the removal of coursework, which has been replaced by a terminal exam. The A-G grading system has also been replaced by numbers from 9-1. The literature review of this study investigates the potential impact the changes have had on gender differences in performance in English, a long-standing concern, which does not appear to have been a factor for consideration by the government during the implementation of the reforms. A mixed methods approach was adopted to explore the perceptions with regard to the changes, of a sample of teachers and students of English in a non-selective faith school in Essex; School A. The results suggest that the reforms have increased stress and anxiety, particularly for students, but it is not thought to have had a significant impact on narrowing the gap in the performance of boys and girls in GCSE English Language. Conclusions from this study would suggest that further research is required by investigating the strategies used by countries with the narrowest gender gaps in reading according to global education rankings, in aiming to adopt them in England.